1967
DOI: 10.1037/h0024371
|View full text |Cite
|
Sign up to set email alerts
|

Nature of positive and negative incentive-motivational effects on general activity.

Abstract: Reinforcement-linked or incentive-motivational changes in general activity were studied by classically conditioning thirsty rats with CS+ (US: water) and CS -(US: electric shock), and, in another situation, measuring their activity in the presence and absence of CSs. In Experiment 1, rats were conditioned while held inactive in restrainers; in Experiment 2, the incidence of perambulation, grooming, and sitting was measured; in Experiment 3, drive level was varied. As compared to control conditions, CS+ increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
1
1

Year Published

1971
1971
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(28 citation statements)
references
References 14 publications
3
23
1
1
Order By: Relevance
“…The number of crossings during the CS period was greater than the pre-CS period for the 35-sec ITI (t = 3.04, df= 15, p< .01) and for the 5-min ITI (t = 5.93, df = 15, P < .001). The facilitative effects of CS introduction are clearly inconsistent with views of the CS as an elicitor of freezing responses in either a fear-conditioning (Bindra & Palfai, 1967) or an avoidance-learning situation (Weiss, Krieckhaus, & Conte, 1968), but suggest conversely that the CS introduction reduces freezing responses, possibly in the manner suggested by Blanchard & Blanchard (1969), increasing initial response rate and thus increasing the prob ability of adaptive responding.…”
mentioning
confidence: 41%
“…The number of crossings during the CS period was greater than the pre-CS period for the 35-sec ITI (t = 3.04, df= 15, p< .01) and for the 5-min ITI (t = 5.93, df = 15, P < .001). The facilitative effects of CS introduction are clearly inconsistent with views of the CS as an elicitor of freezing responses in either a fear-conditioning (Bindra & Palfai, 1967) or an avoidance-learning situation (Weiss, Krieckhaus, & Conte, 1968), but suggest conversely that the CS introduction reduces freezing responses, possibly in the manner suggested by Blanchard & Blanchard (1969), increasing initial response rate and thus increasing the prob ability of adaptive responding.…”
mentioning
confidence: 41%
“…Pretest shock, which can be thought of as analogous to having been bitten, not only increases tonic immobility duration in many species (Edson & Gallup, 1972;Gallup, Creekmore, & Hill, 1970;Gallup, Nash, Potter, & Donegan, 1970), but also profoundly suppresses movement in both rodents and avians and vocalization in birds (Anderson, Crowell, Koehn, & Lupo, 1976; Baron, 1964;Blanchard & Blanchard, 1969;Gallup & Suarez, 1980; Levine, Madden, Conner, Moskal, & Anderson, 1973;Montevecchi et al, 1973;Pinel, Corcoran, & Malsbury, 1971). Similarly, a cue previously paired with shock, or which, by analogy, signals an impending predatory encounter, both prolongs tonic immobility (Gallup, Rosen, & Brown, 1972) and inhibits activity and vocalization in an open field (Bindra & Palfai, 1967;Gallup & Suarez, 1980;Mikulka, Kendall, Constantine, & Porterfield, 1972;Murai, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…In this way, Bindra and Palfai (1967) showed that rats displayed more locomotion and less grooming in response to a conditioned stimulus that predicted the presence of water. Of relevance to the present experiment is the demonstration that rats would sniff at a stimulus that predicted brain stimulation in the lateral hypothalamus (Peterson, 1975).…”
Section: Discussionmentioning
confidence: 99%